Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $$f(x)=\frac{x}{x-1},$$ what is $f^{-1}(f^{-1}(x))$ and $f^{-1}(f^{-1}(f^{-1}(x)))$?

Please help to evaluate if you know. This confuse me a lot! Thanks in advance. is those able to express in term of $x$?

share|cite|improve this question
Hint: $y=f^{-1}(x)=\frac{x}{x-1}$. – Tapu Oct 11 '11 at 23:59
@Swapan - may you explain how do you get your hint? – Victor Oct 12 '11 at 0:01
FYI "special functions" has a very specific meaning in mathematics. There are several monographs filled with curious results about the properties of these functions. For example this. – kahen Oct 12 '11 at 0:02
@Victor, I have edited to start from $y=f(x)\Rightarrow x=f^{-1}(y)$. – Tapu Oct 12 '11 at 0:08
up vote 2 down vote accepted

The inverse of that function is itself

$$f(x) = f^{-1}(x)$$


Find the inverse by replace $f(x)$ with $x$ and all $x$'s with $f^{-1}(x)$, then solving for $f^{-1}(x)$

$$f(x) = x/(x - 1)$$ $$x = f^{-1}(x)/(f^{-1}(x) - 1)$$ $$x*(f^{-1}(x) - 1) = f^{-1}(x)$$ $$x*f^{-1}(x) - x = f^{-1}(x)$$ $$x*f^{-1}(x) = f^{-1}(x) + x$$ $$x*f^{-1}(x) - f^{-1}(x) = x$$ $$f^{-1}(x)(x - 1) = x$$

$$f^{-1}(x) = x/(x - 1)$$

share|cite|improve this answer
WAIT. If $f = f^{-1}$, then $f^{-1}\circ f^{-1}$ is the identity, not $f^{-1}$ again... – GEdgar Oct 12 '11 at 0:08
@GEdgar you're right, sorry. I was thinking of f inverted twice instead of f inverse applied to itself – Paulpro Oct 12 '11 at 0:11
@GEdgar - what do you mean and how do you get that? – Victor Oct 12 '11 at 0:41
@Victor: Try computing it yourself! – GEdgar Oct 12 '11 at 1:43

It’s easy enough to solve for $f^{-1}$, as PaulPRO did in his answer, but in this case it’s also fairly easy to see intuitively why $f$ is its own inverse. First divide it out: $$f(x) = \frac{x}{x-1} = 1 + \frac1{x-1}.$$ To calculate $f(x)$ from $x$ you first subtract $1$ to get $x-1$. Then you take the reciprocal to get $\dfrac1{x-1}$. And finally you add $1$ to get $1+\dfrac1{x-1}$.

Now what happens when you try to reverse the action of $f$? You have to subtract $1$, take the reciprocal, and add $1$, which is exactly what $f$ did in the first place. Thus, $f^{-1}$ must be the same function as $f$.

To make this a bit less informal, notice that what we’ve actually done is split $f$ up as a composition of three functions, which can be pictured as follows: $$x \stackrel{g}\longmapsto x-1 \stackrel{h}\longmapsto \frac1{x-1} \stackrel{j}\longmapsto 1+\frac1{x-1},$$ with $f=j\circ h\circ g$.

Clearly $g$ (subtracting $1$) and $j$ (adding $1$) are inverses of each other, so $j=g^{-1}$, $f=g^{-1}\circ h \circ g$, and we can improve the picture: $$x \stackrel{g}\longmapsto x-1 \stackrel{h}\longmapsto \frac1{x-1} \stackrel{g^{-1}}\longmapsto 1+\frac1{x-1}.\tag{1}$$ Note that $h$ is its own inverse: if you take the reciprocal twice, you’re back where you started.

It’s a basic fact that if the functions involved are invertible, $(\phi\circ\psi)^{-1}=\psi^{-1}\circ\phi^{-1}$, so $f^{-1}=$ $(g^{-1}\circ h\circ g)^{-1} = g^{-1}\circ h^{-1} \circ (g^{-1})^{-1} = g^{-1}\circ h \circ g = f$. In more detail, $f^{-1}$ must reverse the chain of transformations shown in $(1)$: $$1+\frac1{x-1} \stackrel{(g^{-1})^{-1}}\longmapsto \frac1{x-1} \stackrel{h^{-1}}\longmapsto x-1 \stackrel{g^{-1}}\longmapsto x.$$ Since $(g^{-1})^{-1}=g$ and $h^{-1}=h$, this is simply $$1+\frac1{x-1} \stackrel{g}\longmapsto \frac1{x-1} \stackrel{h}\longmapsto x-1 \stackrel{g^{-1}}\longmapsto x,$$ with exactly the same composition of simpler functions as in $(1)$.

share|cite|improve this answer

Part 1 - Finding the inverse function

It may help you to look at the definition and some examples at here: (inverse function link-1

1-replace f(x) with y. This is done to make the rest of the process easier.


2-Replace every x with a y and replace every y with an x.


3-Solve the equation from Step 2 for y.

$y=\frac{x}{x-1},$ Note that this is the same as the original f(x), but this is not always the case.

4-Replace y with $f^{-1}(x)$ In other words, we’ve managed to find the inverse at this point!


Part 2 - Finding $f^{-1}(f^{-1}(f^{-1}(x)))$

to find $f^{-1}(f^{-1}(f^{-1}(x)))$, we find $f^{-1}(z)$ where $z=f^{-1}(f^{-1}(x))$

using $f^{-1}(x)=\frac{x}{x-1},$ replace the value of x by $x/(x-1)$

$z=(f^{-1}(f^{-1}(x)) = ([x/(x-1)])/([x/(x-1)]-1)$

simplifying, you get:


now $f^{-1}(z)$ = $f^{-1}(x)$ which is = $\frac{x}{x-1},$



share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.